An Essential Role of Antibodies in the Control of Chikungunya Virus Infection - Lum, Fok-Moon; Teo, Teck-Hui; Lee, Wendy W L; Kam, Yiu-Wing; Rénia, Laurent; Ng, Lisa F P (The Journal of immunology (1950), 2013)
In recent years, Chikungunya virus (CHIKV) was responsible for epidemic outbreaks in intertropical regions. Although acquired immunity has been shown to be crucial during CHIKV infection in both humans and mice, their exact role in the control of CHIKV infection remains unclear. In this study, wild-type (WT), CD4−/−, and B cell (μMT) knockout mice were infected with CHIKV. Sera were taken at different days postinfection and measured for anti-CHIKV Ab levels. Isotype and neutralizing capacity of these Abs were assessed in vitro, and specific linear epitopes were mapped. Viremia in CHIKV-infected μMT mice persisted for more than a year, indicating a direct role for B cells in mediating CHIKV clearance. These animals exhibited a more severe disease than WT mice during the acute phase. Characterization of CHIKV-specific Abs revealed that anti-CHIKV Abs were elicited early and targeted epitopes mainly at the C terminus of the virus E2 glycoprotein. Furthermore, CD4−/− mice could still control CHIKV infection despite having lower anti-CHIKV Ab levels with reduced neutralizing capacity. Lastly, pre-existing natural Abs in the sera of normal WT mice recognized CHIKV and were able to partially inhibit CHIKV. Taken together, natural and CHIKV infection–induced specific Abs are essential for controlling CHIKV infections.